2021
DOI: 10.1021/jacs.0c11980
|View full text |Cite
|
Sign up to set email alerts
|

Role of the A-Site Cation in Low-Temperature Optical Behaviors of APbBr3 (A = Cs, CH3NH3)

Abstract: APbBr3 (A = Cs, CH3NH3) are prototype halide perovskites having bandgaps of 2.30–2.35 eV at room temperature, rendering their apparent color nearly identical (bright orange but opaque). Upon optical excitation, they emit bright photoluminescence (PL) arising from carrier recombination whose spectral features are also similar. At 10 K, however, the apparent color of CsPbBr3 becomes transparent yellow, whereas that of CH3NH3PbBr3 does not change significantly due to the presence of an indirect Rashba gap. With i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 59 publications
4
28
0
Order By: Relevance
“…Figure 3c shows a threshold behavior in the fluence-dependent PL intensity detected at the lasing wavelength. These observations are very similar to previous studies, e.g., the work of Zhu et al, in which they assign this low-energy emission to the plasmonic emission and claim a normal photon lasing due to population inversion 44 . For our case, the density of the excited particle is estimated to be 1.6 × 10 18 cm −3 at I p of ~10 μJ cm −2 (see Note 2 in Supplementary Information).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 3c shows a threshold behavior in the fluence-dependent PL intensity detected at the lasing wavelength. These observations are very similar to previous studies, e.g., the work of Zhu et al, in which they assign this low-energy emission to the plasmonic emission and claim a normal photon lasing due to population inversion 44 . For our case, the density of the excited particle is estimated to be 1.6 × 10 18 cm −3 at I p of ~10 μJ cm −2 (see Note 2 in Supplementary Information).…”
Section: Resultssupporting
confidence: 92%
“…At the pump fluence I p of ~3.8 μJ cm −2 , a PL signal with asymmetric spectral profile is observed in an energy range of ~2.3-2.4 eV. This is a typical spectral response of CsPbBr 3 crystal at RT 31 , whereas the origin of asymmetric spectral shape is still under discussion 8,31,44,45 . Figure 3b exhibits a colormap of the I p -dependent normalized PL intensities.…”
Section: Resultsmentioning
confidence: 89%
“…For example, increasing the size of the A‐site cation from Cs + to MA to FA narrows the bandgap due to decreased octahedral tilting. [ 8,9 ] Furthermore, cryogenic studies have demonstrated that the A‐site cation also impacts the temperature‐dependent optical [ 10–17 ] and structural properties. [ 14,15,18–24 ] Temperature‐dependent neutron/X‐ray diffraction and photoluminescence (PL) measurements on MAPbBr 3 revealed that the MA cation transformation from an ordered to a disordered state is correlated with an increased integrated PL intensity, and is also suggested to induce the orthorhombic to tetragonal phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,8 ] Regarding the latter, for example, the basic issue such as “the identity of optical excitation at room temperature” is still controversial, because there are contradicting evidences for two candidates, free carriers and excitons. [ 9,10 ] The key question is the stability of the exciton against thermal ionization of the constituents. The exciton binding energy φ X in 3D HPs such as MAPbX 3 (MA = CH 3 NH 3 , X = I, Br, Cl) ranges from 15 meV to 70 meV, [ 9,11,12 ] which is indeed comparable to room temperature (≈26 meV), and therefore, an exciton may or may not be stable.…”
Section: Introductionmentioning
confidence: 99%